Experience of Using Operated Roofs Abroad - Latipovich, Tabibov Abduvoris (International Journal on Orange Technologies, 2023)
This article analyzes wildlife and architecture, are inextricably linked, and that huge areas of the roofs of industrial, residential and public buildings, underground structures make up an indispensable reserve of cities.